Understanding Ahkam Verses: Critical Analysis of Tafsir bi al-Lisān KH. Ahmad Bahauddin Nursalim - Nur Mahbubah; M. Ziyad Ulhaq; Muhammad Ulinnuha (Lembaga Yasin AlSys, 2026)
The growing dissemination of Qur’anic interpretation through digital platforms has expanded public access to Islamic scholarship; however, the hermeneutical characteristics and socio-legal relevance of orally delivered interpretations of legal verses remain insufficiently examined. This study aimed to analyze the interpretive methods employed by KH Ahmad Bahauddin Nursalim (Gus Baha) in his oral exegesis of aḥkām verses on the Santri Gayeng YouTube channel and to assess their relevance to contemporary family ethics and religious education. The study employed qualitative library research with a case-study approach. Recorded exegesis sessions were transcribed and analyzed thematically using relevant literature on tafsīr, uṣūl al-fiqh, and religious pedagogy. The findings indicate that Gus Baha employs a communicative hermeneutical approach characterized by the clarity of tafsīr bi al-lisān, thematic concision associated with the mawḍūʿī method, and a balanced integration of tafsīr bi al-maʾthūr and raʾy. This approach prioritizes accessibility and ethical persuasion for non-specialist Indonesian audiences. His interpretation of marriage-related verses emphasizes honoring wives and children as religious obligations, promoting affectionate and trust-based child-rearing grounded in prophetic exemplarity, and contextualizing prohibitions concerning dowry reclamation and unlawful marriages within the socioeconomic realities of historical Arabian society. His interpretation also foregrounds maqāṣid and intention in advancing rehabilitative marital ethics. These findings demonstrate that Gus Baha’s oral exegesis effectively translates textual authority into accessible, family-centered moral guidance with potential relevance to religious education and social policy. Nevertheless, caution is required regarding claims of naskh and mansūkh and the limited capacity of concise, anecdotal exposition to address structural concerns such as patriarchy and unequal household power relations. This study contributes to contemporary Qur’anic hermeneutics by elucidating the pedagogical and socio-legal significance of digital oral exegesis and provides a foundation for empirical and juridical research on its influence on household practices, legal interpretation, and curriculum development.